THE IMPACT OF SUSTAINABILITY REPORTING ON FIRM VALUE IN INDONESIA’S CONSUMER SECTOR FIRMS - Angelica Kesturi Wiharjo; Agustin Ekadjaja (International Journal of Application on Economics and Business, 2024)
The purpose of this study is to obtain empirical evidence on the effect of sustainability reports on firm value in non-cyclical and cyclical companies in Indonesia. In this research, the data collected comes from financial statements and sustainability reports of consumer sector companies on the Indonesia Stock Exchange. The sample collection technique used is purposive sampling. From the collection techniques used, there were 22 companies that met the sample criteria, bringing the total sample to 44. The study period is 2021-2022. The collected data tested using classical assumption tests and then regressed using multiple regression analysis. The variables used in this study are divided into two, namely the dependent variable and the independent variable. The dependent variable used is the firm value measured using TOBINS'Q. Meanwhile, the independent variables used were general disclosure (COM), economic (ECON), environmental (ENVI) and social (SOC) in sustainability reports. This study also used control variables, namely leverage (DER) and company size (SIZE). According to the study's findings, the variables COM, ECON, and SOC had no impact on the TOBINS'Q-measured corporate firm value. Meanwhile, the value of the company is significantly influenced by ENVI, DER, and SIZE factors. ENVI and DER have a positive impact on the value of the company, however, SIZE has a negative impact on the value of the company. Simultantly, the independent variables positively and significantly affect dependent variable. It is expected that the results of this research will be useful for investors, companies, educational institutions and society in general.